Yolk sac count matters - Todani, Ashok K.; Todani, Kiralata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Yolk sac is the first anatomical structure identified within the gestational sac at 5+ weeks and is diagnostic of intrauterine pregnancy. It is attached through the yolk stalk with the intestinal cavity of the embryo and is supplied with blood vessels that transport nutritive yolk products to the developing embryo. It provides nutritive, metabolic, endocrine, immunological and haemopoietic functions. The poor quality and early regression of a yolk sac in presence of embryonic heart beats are more specific than the large size of a yolk sac in predicting pregnancy loss. Number of yolk sac is usually indicative of amnionicity, except in select reported cases of monoamniotic twins when two yolk sacs are present. Singleton pregnancies contain only one yolk sac as a rule. We have come across a case of elderly non-diabetic primi gravida where presence of one extra yolk sac has accelerated growth of single foetus by 8 days in early first trimester. We followed it up to 16 weeks of gestation when both yolk sacs disappeared. It was concluded that two yolk sacs conferred extra mileage of growth to the foetus due to doubled yolk sac functions, and this extra growth persisted throughout.